QUESTION-FORMATTED IN CLASSROOM INTERACTION TO ATTRACT PRIMARY SCHOOL STUDENT ATTENTION IN ONLINE CLASSROOM - Sofi Yunianti; Idhoofiyatul Fatin; Nina Veronica (EDUPEDIA, 2022)
Online learning is increasingly used around the world due to covid-19. Therefore, this research aims to investigate on conversation analysis that focuses on how the teacher’s question which can engage students’ interaction in classroom. It is known that it is very complex in engaging students ‘in online class, especially first grade primary students. While prior studies regarding online class interaction has not been scrutinized in detail regarding how teacher’s question and students’ responses. Therefore, this study eager to analyzes the teacher and students’ conversation in online class. This study employed qualitative method. The data collected from a series of classroom zoom video. In addition, the data analysis has three stages. First, reduction the utterance, it is based on the question formatted types. Second, coding the data and analyzed the data based on question formatted types. The third is concluding in order to find in the questions-formatted types in online classroom. The types are preserve the sequential implication, slightly alter the sequential implications, following student’s question, and deviant case. The result illustrates in this research is slightly later the sequential implications as the only type which occurred in first grade primary school online classes. It occurred because in online classes it is very demanding to engage student’s attention in online classroom. It is therefore teacher gave questions and pointed directly to students. Consequently, this study implicates on how the pedagogical insight in teaching online learning.